Dataset for: A 31-year time series of at-sea counts shows a non-significant decline of Marbled Murrelets at Laskeek Bay, Haida Gwaii, 1990-2020 - Pattison, Vivian; Drever, Mark; Bertram, Douglas; Pastran, Sonya; Gaston, Anthony; Dickson, Rian (Zenodo, 2024)
This dataset includes counts of Marbled Murrelets ( Brachyramphus marmoratus ) conducted from a small boat near Laskeek Bay on the east coast of Louise Island, and north of Lyell Island in Haida Gwaii, from 1990 to 2020. The dataset includes counts of Marbled Murrelets observed on the water or flying by. Information is also included on the date, time of day, survey width, and spatial coordinates of the transects where the observation took place. Funding provided by: Environment and Climate Change Canada Crossref Funder Registry ID: https://ror.org/026ny0e17 Award Number: Funding provided by: Laskeek Bay Conservation Society Crossref Funder Registry ID: https://ror.org/033env547 The at-sea survey program of Laskeek Bay Conservation Society began in 1990. Researchers use a small open boat (5 – 5.5 m in length) to survey a set of transects between the small islands of Laskeek Bay and along the shoreline of Louise Island in the spring and summer every year, approximately every 2 weeks. All birds and marine mammals seen are recorded during the surveys, although only Marbled Murrelet observations are included in this dataset. The locations of transects surveyed over time, the number of surveys completed, and the timing have remained relatively consistent over time and were standardized in 2005. The complete survey route (67.6 km) is now conducted annually from early May to mid-July and is surveyed over one to two days. Previously, in some years (1990 and 1993 in particular) surveys were spread over many days. For additional survey methods, see Pastran et al. (2021). Marbled Murrelets are recorded as either floating on the water or flying. Before 1998, birds seen flying were not recorded consistently. Pastran, S.A., Drever, M.C. & Lank, D.B. 2021. Marbled Murrelets prefer stratified waters close to freshwater inputs in Haida Gwaii, British Columbia, Canada. Ornithological Applications 123 (4): 1-17. https://doi.org/10.1093/ornithapp/duab043